2013
DOI: 10.7175/rhc.v4i2.483
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in symptoms experienced by advanced cancer patients: a literature review

Abstract: INTRODUCTION: Advanced cancer patients are multi-symptomatic and require attentive palliative care. As gender differences are apparent in multiple aspects of everyday life, this literature review aims to determine the gender differences seen in the population of advanced cancer patients and the symptoms that they experience. METHODS: A literature review was conducted using the OvidSP Medline database from 1946 to November 2012. Randomized, prospective or retrospective cohort studies on advanced cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
(99 reference statements)
1
1
0
Order By: Relevance
“…Consistent with previous studies [6,[38][39][40], we found that women with cancer were more likely than men to be prescribed antidepressants or other medications. The type of medication prescribed to women may be selected to avoid pharmacokinetic interactions with anticancer drugs such as tamoxifen for breast cancer [26], or to help counteract chemotherapy side effects such as nausea that are more common in women [41]. We also found that the prescription of antidepressants decreased as patients aged, again consistent with previous findings [6,38].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with previous studies [6,[38][39][40], we found that women with cancer were more likely than men to be prescribed antidepressants or other medications. The type of medication prescribed to women may be selected to avoid pharmacokinetic interactions with anticancer drugs such as tamoxifen for breast cancer [26], or to help counteract chemotherapy side effects such as nausea that are more common in women [41]. We also found that the prescription of antidepressants decreased as patients aged, again consistent with previous findings [6,38].…”
Section: Discussionsupporting
confidence: 89%
“…With some studies indicating men with cancer, experience some symptoms more than women, and others reporting women experience more symptoms. [55][56][57][58] In our study, the sample of BC patients included only women, whereas the CRC sample included both men and women. It is possible that this finding may have been influenced by the mix of genders in our CRC sample and may have been similar to the BC findings if we had included only women with CRC in the analysis.…”
Section: Breast Cancermentioning
confidence: 99%